2014
DOI: 10.4103/2321-6646.145578
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and reasons for childhood tooth extraction in Northwest Nigeria

Abstract: Childhood tooth extraction is widespread in developing nations especially in sub-Saharan African owing to high prevalence of oral diseases in the population. Purpose of this study is to analyze the reasons and pattern of tooth extraction among children from Northwest Nigeria. Case records of children <14 years seen at the dental clinic of the Federal Medical centre, Gusau, Zamfara state between January 2011 and December 2012 were retrieved from the Medical Records Department and analyzed for analyzed for gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 18 publications
3
20
0
1
Order By: Relevance
“…Other factors like orthodontic extractions did not contribute much in this study, which is comparable to other studies [29,30] On contrary, in a study, trauma contributed as third most leading factor towards exodontia [31] Other factors leading to extraction contributed insignificantly. This small proportion is also comparable to Alesia K., et al study [32].…”
Section: Discussionsupporting
confidence: 87%
“…Other factors like orthodontic extractions did not contribute much in this study, which is comparable to other studies [29,30] On contrary, in a study, trauma contributed as third most leading factor towards exodontia [31] Other factors leading to extraction contributed insignificantly. This small proportion is also comparable to Alesia K., et al study [32].…”
Section: Discussionsupporting
confidence: 87%
“…Comparable to some previous studies, mandibular teeth were more often extracted than maxillary teeth although other studies observed that maxillary teeth were more often extracted. [ 3 20 21 22 ] The propensity of food and plaque accumulation to occur more around the mandibular teeth, thus increasing susceptibility to caries formation, may be responsible for this observation. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Tooth loss has significant socioeconomic, quality of life general health, and psychological consequences. [ 2 3 ] Indeed, tooth loss has become a global public health concern of immense proportion. [ 3 4 ] Despite being preventable, dental caries and periodontal disease remain the most common reasons for tooth extraction, especially developing nations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations